Penerapan Hak Cuti Melahirkan Bagi Pekerja Perempuan di Sektor Formal - Istiarti, VG. Tinuk (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background:The Policy for Women Labors in the Act No. 1 1951 states that women are not allowed to work 1,5 months before and after bearing a child. However, up to the present time, its implementation is not effective. Objective:This explorative research uses quantitative and qualitative approach which objective is to observe the knowledge, attitude and behavior of the woman labourers towards their right of child birth leave. Method of his research is also aimed at observing the employers in imlementing the child birth leave right of the woman labourers and the ralated constraints of the practices. The qualitiative samples consist of 300 respondens of the woman labourers and the qualitative samples consist of 18 employers â€œDepnakerâ€ staff, 18 SPSI members and 15 woman labourers. Instruments for collecting data are questionaire and interviewguides. Qualitative data are analysed by using frequency distribution while qualitative data are analysed by using content analysis. Result:The research results shows that the knowledge and attitude of the woman labourers towards the rights of child birth leave are good enough. However in practice it is not well implemented as that in the regulation, because employers never give additional wages, such as pregnancy and childbirth allowances despite their agreement to implement it. Conclusion:Most employers are not consistent in implementing the right of child birth leave. It can be seen from the fact that the implementation is met only to each own companyâ€™s condition. Those who have had or are in the process of having PKB for example are more consistent than those who have not. Contraints of the implementation of childbirth leave are as follows: 1). Not all employers well comprehend the right of child births leave, 2). The surveillance and empowerment of Disnaker is not effective, 3) The law enforcement to the employers who break the rules is very weak, and 4). The role of SPSI in giving supervision is not yet significant. Key words: Child birth leave, woman labourers, formal sector